Characterization of a symmetric fishnet metamaterial in the M-band - Huynh, Tran Van; Tung, Bui Son; Khuyen, Bui Xuan; Lam, Vu Dinh; Tung, Nguyen Thanh (Vietnam Journal of Science and Technology, 2020)
We study a symmetric fishnet metamaterial working in the M-band (60 - 100 GHz). Significant effects of the dielectric spacer and the metal pattern on the electromagnetic response were investigated. It was found that the left-handed peak was shifted, enhanced or even destroyed by changing the thickness and the permittivity of dielectric spacer. In addition, we also present the effect of metal pattern properties on the left-handed transmission spectra. The effective medium parameters are calculated using the standard retrieval method.